Lin28A/CENPE Promoting the Proliferation and Chemoresistance of Acute Myeloid Leukemia - Shi, Mingyue; Niu, Junwei; Niu, Xiaona; Guo, Honggang; Bai, Yanliang; Shi, Jie; Li, Weiya; Sun, Kai; Chen, Yuqing; Shao, Fengmin (Frontiers in Oncology, 2021)
The prognosis of chemo-resistant acute myeloid leukemia (AML) is still poor, mainly owing to the sustained proliferation ability of leukemic cells, while the microtubules have a major role in sustaining the continuity of cell cycle. In the present study, we have identified CENPE, a microtubular kinesin-like motor protein that is highly expressed in the peripheral blood of patients with chemo-resistant AML. In our in vitro studies, knockdown of CENPE expression resulted in the suppression of proliferation of myeloid leukemia cells and reversal of cytarabine (Ara-C) chemo-resistance. Furthermore, Lin28A, one of the RNA-binding oncogene proteins that increases cell proliferation, invasion and contributes to unfavorable treatment responses in certain malignancies, was found to be remarkably correlated with CENPE expression in chemo-resistance AML. Overexpression of LIN28A promoted the proliferation and Ara-C chemo-resistance of leukemic cells. RIP assay, RNA pull-down and dual luciferase reporter analyses indicated that LIN28A bound specifically to the promoter region-GGAGA of CENPE. In Addition, the impacts of LIN28A on cell growth, apoptosis, cell cycle progression and Ara-C chemo-resistance were reverted by the knockdown of CENPE. Hence, Lin28A/CENPE has enhanced the proliferation and chemo-resistance of AML and therefore it could be a prospective candidate for AML treatment.